Experimental and Analytical Analysis of Creep of Steel Fibre Reinforced Concrete - Nakov, D., Markovski, G., Arangjelovski, T., Mark, P. (Periodica Polytechnica Budapest University of Technology and Economics, 2017)
To find out the influence of different fibre dosages on the creep of SFRC (Steel fibre reinforced concrete), an experiment was carried out at the Faculty of Civil Engineering–Skopje. The experiment involved 9 specimens manufactured with concrete class C30/37 and reinforced with different amount of fibres (0, 30 and 60 kg/m3). According to the experimental results obtained up to the age of 400 days, the addition of steel fibres had an influence on the creep strains (a decrease of up to 12%). Based on the experimental results, analytical analyses of creep were performed by use of the B3 model and fib Model Code 2010. The analyses were prolonged up to the estimated age of service life of structures of 100 years. According to the B3 model, at the age of 100 years, the decrease of the creep coefficient is 11.1% in the case of the SFRC type C30/37 FL 1.5/1.5, while in the case of C30/37 FL 2.5/2.0, it is 17.8%, when compared to C30/37.
Keywords: creep, experiment, B3 model, fib Model code 2010, SFRC